Expectations concerning retail: a study of clothing and shoe consumers at the bottom of the social pyramid - Antoni, Verner Luis; Basso, Kenny (Review of Business Management, 2016)
Purpose – To understand different perceptions of retail by consumers at the bottom of the social pyramid, to thus understand specific market niches that are a part of the low income segment. Design/methodology/approach – We carried out a survey including 560 cases. We also used cluster and discriminant analysis. Findings – We observed the formation of four groups of customers, which showed significant distinctions in the characteristics considered for choosing a store. Originality/value – The clusters represents a discriminant effort to highlight the differences between consumers considered in the same group of analysis, the bottom of the pyramid. Managerially, retail managers can assess their retail mix, and then drive more focused strategies and operations.